Global perspective and African outlook on additive manufacturing research − an overview - Klenam Desmond Edem Primus; Bamisaye Olufemi Sylvester; Williams Iyanu Emmanuel; van der Merwe Josias Willem; Bodunrin Michael Oluwatosin (Manufacturing Review, 2022)
Additive manufacturing (AM) technologies and advances made globally in medicine, construction, aerospace, and energy sectors are discussed. The paper further explores the current state of AM innovation and development landscape in Africa as a late comer to this area of smart manufacturing. Peer-reviewed and published literature were retrieved from Scopus database from 2005 to 2021 and analysed. In Africa, out of 500 published articles, South Africa has the highest research throughput, whereas about two-thirds of the continent is not actively participating in this burgeoning field. The main AM techniques most widely used are selective laser melting, fused deposition modelling, and direct energy deposition. Globally, there is an interplay of computational (machine learning and mechanistic models) and experimental approaches to understanding the physical metallurgy of AM techniques and processes. Though this trend is consistent with global practices, Africa lags the world in AM technologies, a niche that could leapfrog the manufacturing sector. Thus, Africa need to foster collaborative partnership within and globally to become an active global player in this industry.